Effects of smoking cessation on serum leptin and adiponectin levels - Kryfti, Maria (Tob Induc Dis, 2015)
BACKGROUND: Evidence on the association of leptin and adiponectin and smoking is limited and discordant. Leptin and adiponectin represent the most abundant adipokines in human plasma that play crucial roles in the pathophysiology of metabolic syndrome, atherosclerosis and insulin resistance. Leptin up-regulates the expression of several pro-inflammatory cytokines and is increased upon weight gain. Adiponectin has been shown to possess insulin sensitizing, anti -inflammatory and anti-atherogenic properties and is increased upon weight reduction. Our aim was to assess the effects of smoking cessation on serum leptin and adiponectin levels. METHODS: We assessed the changes in serum leptin and adiponectin levels, serum CRP levels and BMI in apparently healthy smokers after 3 and 6 months of abstinence from smoking. Successful cessation was confirmed by an exhaled carbon monoxide measurement. 26 healthy non-smokers were recruited as controls. RESULTS: Among the sample group, 32 subjects had quitted smoking at 3 months and 29 subjects at 6 months. Samples’ leptin increased significantly from baseline to three months (mean change 3.76 ng/ml [95 % CI 0.89, 6.64], p =0.012) and then decreased significantly from three to six months of smoking cessation (mean change -4,29 ng/ml [95 % CI −7.34, −6.64], p = 0.008). Samples’ adiponectin increased significantly from baseline to three months of abstinence from smoking (mean change 2.34 [95 % CI −0.05, 4.73], p −0.05). BMI was significantly increased (mean change 2.03 kg/m(2) [95 % CI 1.60, 2.46], p <0.05), while CRP decreased significantly from baseline to 6 months of smoking cessation (mean change −0.68 mg/dl [95 % CI −1.06, −0.30], p = 0.001). CONCLUSIONS: Smoking quitters’ leptin levels appear to increase 3 months after smoking cessation and then decrease from 3 to 6 months of abstinence from smoking. Adiponectin levels increase during the first trimester of smoking cessation. The decrease in CRP levels indicates that the low grade inflammation observed in smokers is gradually restored. The alterations of serum leptin and adiponectin after 6 months of smoking cessation suggest the same but do not reach statistically significant levels. Weight gain and changes in fat distribution may attenuate the beneficial effects of smoking cessation.